2011
DOI: 10.3892/ol.2011.380
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A and changes in a tumor-bearing mouse model with Lewis lung cancer

Abstract: Abstract. Vascular endothelial growth factor-A (VEGF-A)affects tumor growth and metastasis through stimulation of angiogenesis. The purpose of this study was to describe features of Lewis lung cancer (LLC) in mice and compare the serum VEGF-A levels with those of normal control mice. Two groups of mice were compared: one was subcutaneously injected with LLC cells (n=16) and the other served as the normal control (n=6). The serum VEGF-A levels were measured by ELISA prior to inoculation, and at 7, 21 and 35 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In the present study, we identified that LLC-secreted VEGF functions as a vasoactive factor that is able to induce the permeability through Rac1. Serum murine VEGF (mVEGF) levels were increased to 0.1 ng/ml in mice bearing LLC xenografts, this value is completely consistent with the literature that has also shown the serum levels of VEGF in mice bearing LLC xenografts [ 17 ], however, in our in vitro experiments, we activated Rac1 in HUVEC in response to recombinant human VEGF-A (rhVEGF-A) at 50 ng/ml that is much greater than serum mVEGF levels of mice bearing either LLC xenografts or hematogenously metastatic LLC. We suggest that the bioactivity of circulating mVEGF is equivalent to that of in vitro rhVEGF-A in induction of endothelial Rac1 activation.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we identified that LLC-secreted VEGF functions as a vasoactive factor that is able to induce the permeability through Rac1. Serum murine VEGF (mVEGF) levels were increased to 0.1 ng/ml in mice bearing LLC xenografts, this value is completely consistent with the literature that has also shown the serum levels of VEGF in mice bearing LLC xenografts [ 17 ], however, in our in vitro experiments, we activated Rac1 in HUVEC in response to recombinant human VEGF-A (rhVEGF-A) at 50 ng/ml that is much greater than serum mVEGF levels of mice bearing either LLC xenografts or hematogenously metastatic LLC. We suggest that the bioactivity of circulating mVEGF is equivalent to that of in vitro rhVEGF-A in induction of endothelial Rac1 activation.…”
Section: Discussionsupporting
confidence: 90%
“…Tumor angiogenesis, the formation of new blood vessels from endothelial precursors within tumors, is a prerequisite step for growth and progression of solid malignancies [ 6 ]. Vascular endothelial growth factor (VEGF) is an essential player in tumor angiogenesis and mediates tumor aggressiveness [ 7 - 9 ]. Monocyte chemotactic protein-1 (MCP-1), a key CC chemokine responsible for trafficking and activation of monocytes/macrophages has been recognized as an important angiogenic chemokine [ 10 , 11 ]; it also plays a critical role in solid tumors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental metastases were induced by intravenous injection of 5 × 10 4 LLC1 cells [ 10 ]. Mice intravenously received either 5 × 10 5 MSCs or saline one week after injection of LLC1 cells.…”
Section: Methodsmentioning
confidence: 99%